The origins and growth of freemasonry in South Africa, 1772-1876 - Cooper, Alan Amos (Department of Historical Studies, 2016)
This thesis sets out to examine the historical growth of Freemasonry at the Cape and its expansion eastwards and northwards. It covers the period from the beginnings of Freemasonry in Cape Town in 1772 until 1876 when English and Dutch branches of the Craft had become involved in the political issues of that time. In doing so it tries to examine the effect of social, economic and political events in South Africa on Dutch and English Freemasonry, making the somewhat bold claim that this masonic movement acted often as a mirror to these events. The study confines itself to the historical aspects of freemasonry and does not endeavour to portray esoteric changes that took place within the Craft. Specifically it details the start of Freemasonry on the continent of Africa by Abraham Chiron and the founding of the first lodge, De Goede Hoop, a Netherlandic lodge, its decline and resurgence during the Dutch, British and Batavian occupations and the beginnings of English Freemasonry under the final British occupation. From then it sets out the expansion and changes in organisation brought about by several masonic personalities, many of whom were leading figures in the society of their time.